Electronic structure of spherical quantum dots using coupled cluster method - Heidari, Ideh; Pal, Sourav; Pujari, B. S.; Kanhere, Dilip G. (Journal of Chemical Physics, 2007)
2, 6, 12, and 20 electron quantum dots have been studied using coupled cluster at singles and doubles level and extensive multireference coupled cluster (MRCC) method. A Fock-space version of MRCC (FSMRCC) containing single hole-particle excited determinants has been used to calculate low-lying excited states of the above system. The ionization potential and electron affinity are also calculated. The effect of correlation energy on excitation energy and charge density is shown by calculating them at the high density region (low value of density parameter r(s)) and at the low density region (high value of density parameter r(s)). (c) 2007 American Institute of Physics.

Electric field response of molecular reactivity descriptors: a case study - Kar, Rahul; Pal, Sourav (Theoretical Chemistry Accounts, 2008)
In the present article, we study the influence of external electric field on the density-based global and local reactivity descriptors using examples of some planar nonlinear polyatomic molecules with C-2V point group symmetry. The study mainly involves the application of weak electric field in a direction along the principal axis and along its perpendicular direction. We also discuss the strength of the electric field studied in this work in terms of the strength of the molecular interaction. The work is expected to throw light on the effect of interactions within the above range on reactivity descriptors. Results are presented for a few prototype molecules.
Keywords: electric field; molecular interaction; planar nonlinear polyatomic molecules; Reactivity descriptors

Effect of solvents having different dielectric constants on reactivity: a conceptual DFT approach - Kar, Rahul; Pal, Sourav (International Journal of Quantum Chemistry, 2010)
Conceptual density functional theory is exploited to understand the reactivity in a medium of solvents with increasing dielectric constants. Aprotic as well as protic solvents are used for this study. It is found that the global parameters, such as chemical potential and hardness, decrease from gas phase to solvent phase with increasing dielectric constant. However, it is observed that the Fukui functions of the reactive atoms increase significantly with the dielectric constants of the aprotic solvents while for the protic solvents the variation of the reactivity indices is insignificant. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 110: 1642-1647, 2010
Keywords: COSMO; DFT; dielectric constant; Reactivity descriptors; solvent effect

Effect of triples to dipole moments in fock-space multireference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2011)
In this paper, we present the new implementation of partial triples for the dipole moment of doublet radicals in Lagrangian formulation of Fock-space multireference coupled cluster (A-FSMRCC) response method. We have implemented a specific scheme of noniterative triples, in addition to singles and doubles schemes, which accounts for the effects appearing at least at the third order in dipole moments. The method is applied to the ground states of OH, OOH, HCOO, CN, CH, and PO radicals.

Equation-of-motion coupled-cluster method for the study of shape resonance - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2012)
The equation-of-motion coupled-cluster method (EOM-CC) is applied for the first time to calculate the energy and width of a shape resonance in an electron-molecule scattering. The procedure is based on inclusion of complex absorbing potential with EOM-CC theory. We have applied this method to investigate the shape resonance in e(-)N(2), e(-)CO, and e(-)C(2)H(2). (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4729464]

Extended coupled cluster for Raman and infrared spectra of small molecules - Joshi, Sayali P.; Dutta, Achintya Kumar; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
In this paper we study the harmonic vibrational frequencies, infrared (IR) intensities, Raman intensities and depolarization ratio using extended coupled cluster method. Raman and IR intensities are mixed derivatives of energy with respect to the electric field and geometric perturbation whereas vibrational frequencies are derivatives of energy with respect to geometry. We use semi-numerical approach to obtain these derivatives. We have studied the effect of electron correlation and basis set for the above properties. We compare our results with non-variational coupled cluster and experimental values, wherever available. We have studied HF, BH, CH+, CO and H2CO molecules in different basis sets. For HF molecule, benchmarking is done with full CI values and basis set convergence is studied for this molecule. Effect of triples is studied for all the molecules. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Extended coupled cluster; IR and Raman spectroscopy; Mixed derivatives

Electronic transition dipole moments and dipole oscillator strengths within fock-space multi-reference coupled cluster framework: an efficient and novel approach - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
Within the Fock-space multi-reference coupled cluster framework, we have evaluated the electronic transition dipole moments, which determine absorption intensities. These depend on matrix elements between two different wave functions (e. g., ground state to the excited state). We present two different ways, to calculate these transition moments. In the first method, we construct the ground and excited state wave functions with the normal exponential ansatz of Fock-space coupled cluster method and then calculate the relevant off-diagonal matrix elements. In the second approach, we linearize the exponential form of the wave operator which will generate the left vector, by use of Lagrangian formulation. The right vector is obtained from the exponential ansatz. In order to relate the transition moments to oscillator strengths, excitation energies need to be evaluated. The excitation energies are obtained from the Fock-space multi-reference framework. The transition dipole moments of the ground to a few excited states, together with the oscillator strengths of a few molecules, are presented. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4793277]

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Effect of silicon doping on the reactivity and catalytic activity of gold clusters - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2014)
Doping is known to be an excellent and simple way of catalyst design. Although notable progress has been made in understanding the reactivity and catalytic activity of gas-phase and supported gold clusters, very few studies have been carried out on the doped gold clusters. In the present work, we have carried out density functional theory calculations to investigate the effect of silicon doping on the reactivity and catalytic activity of gold nanoclusters. The present work particularly focuses on the adsorption and activation of molecular oxygen on the pristine and silicon-doped gold clusters. The results confirm that the silicon-doped Au7Si cluster shows considerable binding and activation of the O-2 molecule in comparison to the pristine Au-8 cluster as reflected in the relevant geometrical parameters (O-O and Au-O bond lengths) and O-O stretching frequency. However, silicon doping has no contrasting effect on the reactivity and catalytic activity of the Au-7 cluster. In addition to the stronger binding and activation of the O-2 molecule, the doped Au7Si cluster leads to a significant reduction in the activation barrier (0.57 eV) for the environmentally important CO oxidation reaction in contrast to the catalytically inactive pristine Au-8 cluster (1.22 eV). Thus, our results highlight the critical role of doping foreign impurities for future endeavors in the field of gold nanocatalysis.

Electronic transition dipole moment: a semi-biorthogonal approach within valence universal coupled cluster framework - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2014)
Electronic dipole strengths (square of transition moments) and oscillator strengths are evaluated for various transitions, arising from the ground state to a few valence excited states. Parallel to two other methods of calculating the dipole strength within the Fock-space multireference coupled cluster framework, a new semi-biorthogonal approach is formulated and implemented in this article. This semi-biorthogonal approach can evaluate dipole strengths at a lower computational effort than the biorthogonal approach without compromising on the accuracy. This new method is compared and tested against the previously developed expectation value and biorthogonal approach for various molecular transitions. (C) 2014 Wiley Periodicals, Inc.
Keywords: electronic transition dipole; Fock-space; oscillator strength; semi-biorthogonal expectation value

Enhanced interaction of molecular oxygen with amino acid complexes of silver and gold clusters - Manzoor, Dar; Pal, Sourav (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
Density functional theory calculations have been carried out to study the effect of amino acid adsorption on the reactivity of silver and gold clusters with molecular oxygen. It is found that the amino acids glycine and alanine form stable complexes with both Ag-4 and Au-4 clusters. However, the extent of interaction is more in the case of the Au-4 cluster, as reflected from the increase in binding energy in the amino acid Au-4 complexes. Our results confirm that the adsorption of amino acids glycine and alanine enhances the reactivity of Ag-4 and Au-4 clusters towards O-2 molecule. The enhanced reactivity of O-2 molecule towards the amino acid metal cluster complexes is manifested by an increase in the O-2 binding energy and a decrease in the M-O (M = Ag, Au) bond length. Moreover, it is found that the co-adsorption of amino acids and O-2 molecule on the Ag-4 and Au-4 clusters is cooperative.
Keywords: Amino acid complexes; Density functional calculations; Gold clusters; Metal clusters; Silver clusters; Theoretical chemistry

Electron attachment to DNA and RNA nucleobases: an EOMCC investigation - Dutta, Achintya Kumar; Sengupta, Turbasu; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2015)
We report a benchmark theoretical investigation of both vertical and adiabatic electron affinities of DNA and RNA nucleobases: adenine, guanine, cytosine, thymine, and uracil using equation of motion coupled cluster method. The vertical electron affinity (VEA) values of the first five states of the DNA and RNA nucleobases are computed. It is observed that the first electron attached state is energetically accessible in gas phase. Furthermore, an analysis of the natural orbitals exhibits that the first electron attached states of uracil and thymine are valence-bound in nature and undergo significant structural changes on attachment of an extra electron, which reflects in the deviation of the adiabatic electron affinity (AEA) than that of the vertical ones. Conversely, the first electron attached states of cytosine, adenine, and guanine are in the category of dipole-bound anions. Their structure, by and large, remain unaffected on attachment of an extra electron, which is evident from the observed small difference between the AEA and VEA values. VEA and AEA values of all the DNA and RNA nucleobases are found to be negative, which implies that the first electron attached states are not stable rather quasi bound. The results of all previous theoretical calculations are out of track and shows large deviation with respect to the experimentally measured values, whereas, our results are found to be in good agreement. Therefore, our computed values can be used as a reliable standard to calibrate new theoretical methods. (c) 2015 Wiley Periodicals, Inc.
Keywords: DNA-RNA bases; electron affinity; EOMCC

EOMIP-CCSD(2)*: an efficient method for the calculation of ionization potentials - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2015)
A new approximation within the domain of EOMIP-CC method is proposed. The proposed scheme is based on the perturbative truncation of the similarity transformed effective Hamiltonian matrix. We call it the EOMIP-CCSD(2)* method, which scales as noniterative N-6 and its storage requirement is very less, compared to the conventional EOMIP-CCSD method. The existing EOMIP-CCSD(2) method has a tendency to overestimate the ionization potential (IP) values. On the other hand, our new strategy corrects for the problem of such an overestimation, which is evident from the excellent agreement achieved with the experimental values. Furthermore, not only the ionization potential but also geometry and IR frequencies of problematic double radicals are estimated correctly, and the results are comparable to the CCSD(T) method, obviously at lesser computational cost. The EOMIP-CCSD(2)* method works even for the core ionization and satellite IP, where the earlier EOMIP-CCSD(2) approximation dramatically fails.

Electron detachment and subsequent structural changes of water clusters - Das, Susanta; Sengupta, Turbasu; Dutta, Achintya Kumar; Pal, Sourav (Journal of Physical Chemistry A, 2016)
A cost-effective equation of motion coupled cluster method, EOMIP-CCSD(2), is used to investigate vertical and adiabatic ionization potential as well as ionization-induced structural changes of water clusters and compared with CCSD(T), CASPT2, and MP2 methods. The moderate N-5 scaling and low storage requirement yields EOMIP-CCSD (2) calculation feasible even for reasonably large molecules and clusters with accuracy comparable to CCSD(T) method at much cheaper computational cost. Our calculations shed light on the authenticity of EOMIP-CCSD(2) results and establish a reliable method to study of ionization energy of molecular clusters. We have further investigated the performance of several classes of DFT functionals for ionization energies of water clusters to benchmark the results and to get a reliable functionals for the same.

Endohedrally doped gold nanocages: efficient catalysts for O-2 activation and CO oxidation - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Physical Chemistry Chemical Physics, 2016)
Gold nanocages are the most attractive catalytic materials as all the atoms in the cage type clusters reside on the surface, making them available for chemisorption by reacting molecules. Due to a hollow space at the center, their chemical and catalytic properties can be tuned effectively and easily by endohedral doping. While a significant experimental and theoretical understanding is currently available on the structural and electronic properties of doped gold cages, very little information is available on their reactivity and catalytic behavior. In the present work, with the help of density functional theory calculations we demonstrate that endohedral doping leads to a notable increase in the binding energy of molecular oxygen on the gold nanocages. The enhancement in the O-2 binding energy on the doped gold cages is also confirmed by a significant decrease in the Au-O and an increase in the O-O bond lengths, corroborated by a red shift (similar to 250 cm(-1)) in the O-O stretching frequency as compared to the pristine cage. Furthermore, interestingly, the doped gold cages show very low activation barriers for the environmentally important CO oxidation reaction as compared to the pristine gold cage. Importantly, the decrease in the barrier height is comparatively greater for the rate limiting step of O-O-C-O intermediate formation and as a result the CO oxidation is expected to be more facile on the doped gold cages. Thus, the current study highlights the role of heteroatom doping in imparting new chemical and catalytic properties to gold cages and is expected to spur further research in the design of efficient gold nanocatalysts.

Effect of ligand attachment on the C-I bond dissociation process on aluminum nanoclusters: a DFT investigation - Sengupta, Turbasu; Samanta, Bipasa; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The influence of the ligand attachment on the activation process of carbon halogen bond on small sized aluminum nanoclusters are investigated using density functional theory. Attaching suitable ligand to metal clusters is among the widely popular techniques often used by experimentalists in order to stabilize metastable clusters. In depth theoretical investigations have shown that based on the jellium configuration of the cluster, attaching an electron withdrawing ligand can either make a cluster more reactive toward the C-I dissociation or may convert the cluster relatively inert. The alteration of the activation barriers and other associated parameters due to ligand attachment are included in this paper along with additional calculations and explanations. The study also shows that even the reaction parameters of specific magic clusters can be significantly altered via ligand attachment. The activation process of small molecules on metal clusters are of crucial importance for the development of material science and cluster chemistry. The present investigation will therefore be useful for better understanding of the properties of the ligated clusters as well as may also aid the experimentalists toward controlling the reactivity of a specific cluster as required.

Electronic structure parameter of nuclear magnetic quadrupole moment interaction in metal monofluorides - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2020)
The electronic structure parameter (W-M) of the nuclear magnetic quadrupole moment (MQM) interaction in numerous open-shell metal monofluorides (viz., MgF, CaF, SrF, BaF, RaF, and PbF) is computed in the fully relativistic coupled-cluster framework. The electron-correlation effects are found to be very important for the precise calculation of W-M in the studied molecular systems. The molecular MQM interaction parameter scales nearly as Z(2) in the alkaline earth metal monofluorides, where Z is the nuclear charge of metal. Our study identifies (RaF)-Ra-223 as a good candidate for the experimental search of the nuclear MQM, which can help unravel the physics beyond the standard model in the hadron sector of matter.